2008
DOI: 10.2500/ajr.2008.22.3204
|View full text |Cite
|
Sign up to set email alerts
|

Rhinologic Symptoms and Quality-of-Life in Patients with Churg-Strauss Syndrome Vasculitis

Abstract: Sinonasal symptoms are common at initial presentation of CSS, emphasizing the role of otolaryngologists in its diagnosis. Overall, CSS-related sinonasal morbidity is significant and comparable with that of the general rhinosinusitis population. It predominantly results from symptoms of allergic rhinitis, but a significant proportion of CSS patients also report milder forms of crusting, epistaxis, and of purulent sinusitis, symptoms which are more commonly attributed to patients with WG.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0
8

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 48 publications
(37 citation statements)
references
References 12 publications
1
28
0
8
Order By: Relevance
“…1441 Systemic manifestations of both sarcoidosis and ChurgStrauss syndrome are managed with chemotherapeutic agents, oral corticosteroids ± immune modulators, but like GPA, the literature supports use of medical management while reserving surgical intervention for persistent rhinologic symptoms in select patients. [1442][1443][1444][1445][1446] Given the epithelial abnormalities present in CGD patients, patients should be counseled regarding suboptimal and/or delayed healing that can follow intranasal procedures.…”
Section: Special Considerations In Rhinosinusitis Xiia Rs Specmentioning
confidence: 99%
“…1441 Systemic manifestations of both sarcoidosis and ChurgStrauss syndrome are managed with chemotherapeutic agents, oral corticosteroids ± immune modulators, but like GPA, the literature supports use of medical management while reserving surgical intervention for persistent rhinologic symptoms in select patients. [1442][1443][1444][1445][1446] Given the epithelial abnormalities present in CGD patients, patients should be counseled regarding suboptimal and/or delayed healing that can follow intranasal procedures.…”
Section: Special Considerations In Rhinosinusitis Xiia Rs Specmentioning
confidence: 99%
“…On the other hand, crust formation in the nasal cavity was rather uncommon in patients with chronic rhinosinusitis, but it is common in those with GPA. Previous studies have also reported nasal crusting in patients with EGPA, with the incidence of nasal crusting ranging from 14.2 to 75% [Bacciu et al, 2006;Srouji et al, 2008]. This symptom might reflect vasculitis in the mucosa of the nasal cavity and could be used to distinguish EGPA from chronic rhinosinusitis.…”
Section: Discussionmentioning
confidence: 98%
“…Rhinorrhea, nasal obstructions, crust formation and hyposmia were the major symptoms of EGPA [Srouji et al, 2008]. None of these symptoms, except for crusting, are specific to EGPA, and they are often found in patients with chronic rhinosinusitis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Overall, 80% of CSS patients have active sinonasal symptoms at the time of presentation and worsening of their nasal symptoms may be the main event leading to their diagnosis (Srouji I et al 2008) . Nearly half CSS patients had undergone nasal surgery.…”
Section: Upper Airwaymentioning
confidence: 99%